Morphological Characterization of Emerging Cercariae among Lymnaeid Snails from Barangay Cawongan, Padre Garcia, Batangas, Philippines - Gregorio L. Martin I; Esperanza C. Cabrera (Journal of Parasitology Research)
Background and Objectives. Lymnaeid snails are the known intermediate hosts of the liver fluke Fasciola spp. and therefore play an important role in the parasite’s life cycle. The study is conducted to determine specificity of snail host-parasite interaction and to determine the snail-trematode infection rate by cercarial emergence, characterizing the emerging larvae using standardized key. Materials and Methods. A total of 750 snails were collected from a rice field in Barangay Cawongan, Padre Garcia, Batangas, from November 2016 to March 2017 (n=150/month). Preliminary snail identification was based on morphological features of the shell. Each snail was acclimatized for 24 hours in a 50-ml capacity container before being exposed to strong artificial light. The 150 snails collected per month were grouped into 5 batches (n=30/batch) with each batch receiving different number of light exposures. Emerging cercariae were described and characterized using photo-referencing and standardized keys. All statistical tests were performed at p<0.05 level of significance using SPSS ver. 20. Results. The total cercarial shedding rate of the snails studied, as a measure of the infected snails, was found to be 35.6% and was positively associated with the length of the snail shell [OR = 1.809; 95% CI: 1.471–2.225; p<0.001], but not with the weight [OR = 0.003; 95% CI: 0.00–0.275; p=0.012] and width of the shell [OR = 0.937; 95% CI: 0.672–1.305]. The rates varied from 29.3% to 38.0% based on the frequency of 6-hour light exposure. Appearance of encysted forms increased with increasing number of light exposures [OR = 10.27, 95% CI: 3.04–34.76, p<0.001]. Three distinct cercariae were identified, namely, echinostome, longifurcate-pharyngeate distome cercariae (Strigea cercariae), and the virgulate xiphidiocercaria, with 26.4%, 2.27%, and 0.67% infection monitored by cercarial emergence, respectively. Conclusion. Local lymnaeid snails were infected with a single type of trematode larvae and coinfection with multiple larvae was rare but was encountered.